OWE-35 Multiprofesssional in situ simulation is an effective method of identifying latent patient safety threats. (June 2019) - Jafar, Wisam; Suggitt, Ms Debbie; Uttley, Elizabeth; Jackson, Louisa; Baxter, David
Abstract : Introduction: Identifying errors in the ward environment, healthcare organisation or interaction between the multiprofessional team members is crucial. Such identification may prevent serious mistakes that can occur in high pressure gastroenterology emergencies. Unannounced multiprofessional in situ simulation can be an effective means of identifying latent patient safety threats before they occur. We set up a standardised in situ simulation programme centred around speciality specific emergency scenarios not only to improve skills, team working and communication but also to identify and address latent errors. The in situ faculty consisted of a consultant gastroenterologist; skills tutor; education fellow and director of medical education. Methods: We identified key learning objectives for several different emergency scenarios including: massive upper gastrointestinal haemorrhage; septic shock; post-procedure complications and cardiac arrest. Using a wireless high fidelity simulation manikin we ran 15 unannounced sessions between February 2017 and January 2019. There was a minimum of three faculty in attendance in each of the sessions and an overall total of 67 participants representing the spectrum of different professions including: doctors; nurses; health care assistants and students from nursing, medical, and physician associate backgrounds. Following completion of the scenario a structured debrief was conducted. Latent errors affecting patient safety at an individual, team or organisational level were identified and discussed. Following the scenarios, actions were put in place designed to address the identified errors in a timely fashion. Results: During the 15 unannounced sessions between February 2017 and January 2019 we identified the following latent errors: shortage of Sengstaken-Blakemore tubes, Bair Hugger and a step for CPR on the ward; lack of awareness as to how to activate the major haemorrhage protocol; junior doctors without working pagers; deficiencies in resuscitation skills amongst non-training grade doctors; members of the multiprofessional team forgetting each others' names and parts of the ALS algorithm; not knowing where the oral glucose gel is kept on the ward. Since the identification of these errors corrective measures have included: laminated ALS algorithms attached to the resuscitation trolleys and dedicated major haemorrhage protocol training at junior doctor induction. Equipment shortages including sourcing the relevant equipment has been undertaken by ward management. Dedicated training days for the non-training grade doctors has also been undertaken. Conclusions: In situ simulation is highly effective in identifying latent errors that could have potentially deleterious consequences on patient safety. This allows corrective measures to be undertaken in advance of real-life emergencies.